Spaced out: "Territoriality" in the Fourth Gospel - Neyrey, Jerome H. (HTS teologiese studies, 2002)
The Fourth Gospel is inordinately involved with places and spaces, valuing some, but dis-valuing others. The task of interpreting all such references is greatly aided by the use of the anthropological model of "territoriality” which shows how all peoples 1) classify space, 2) communicate this and 3) control access to or exit from this territory. The classifications might be: public-private, sacred/profane, honorable/shameful, clean/unclean, fixed/fluid, center/periphery and the like. Where appropriate, these classifications are used to interpret the Johannine data on spaces and places, particularly 1) Galilee/Judean, 2) public/in secret, 3) not on this mountain, nor in Jerusalem, 4) whence/whither, 5) in my Father’s house there are many rooms, 6) “in-dwelling” and “being-in” another; and 7) two different worlds.